(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The paper discusses ore fields of RA with industrial porphyry copper mineralization. The use of conceptual and combined models of ore-magmatic system and ore fields, it is possible to pick out prospective ore occurrences and make some prediction at a depth.